2011
DOI: 10.1016/j.sse.2011.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corner angle of trapezoidal and triangular channel cross-sections on electrical performance of silicon nanowire field-effect transistors with semi gate-around structure

Abstract: Structural effects, especially corner angle of upper-corners of trapezoidal and rectangular, and triangular cross-sectional shapes of silicon nanowire field-effect transistors on effective carrier mobility and normalized inversion charge density have been investigated. <100>-directed silicon nanowire field-effect transistors with semi-gate around structure fabricated on (100)-oriented silicon-on-insulator wafers were evaluated. As the upper-corner angle decreased from obtuse to acute angle, we observed an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…However, the values are visibly higher when measured along the u1 and u3 directions as compared to š‘¢ 2 . This is due to the corner effect [20], which is a consequence of the strong electric field in the corners of the nanowire. Near these corners, the top gate TG and the bottom gate BG become very close (see dash circles in the cross-sectional view of Figure 8(d)) and can be viewed as a double-gate MOSFET structure.…”
Section: Resultsmentioning
confidence: 99%
“…However, the values are visibly higher when measured along the u1 and u3 directions as compared to š‘¢ 2 . This is due to the corner effect [20], which is a consequence of the strong electric field in the corners of the nanowire. Near these corners, the top gate TG and the bottom gate BG become very close (see dash circles in the cross-sectional view of Figure 8(d)) and can be viewed as a double-gate MOSFET structure.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the VLS and EBL methods, SiNWs-FET sensors fabricated by WETO method have remarkable advantages such as the controllability of the whole process and the capability of wholesale manufacture [ 21 ]. Additionally, the cross-sections of the SiNWs fabricated by these three methods are circular, square and triangular, respectively, which seriously affects the performance of devices [ 22 , 23 , 24 , 25 , 26 , 27 ]. Here, we compared the sensitivity of the SiNWs-FET sensor fabricated by our WETO method with the others by theoretical analysis and software simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on nanowire channels with different geometry, based on basic material parameters of GaN, have shown that MOSFET with triangular-shaped nanowire channel exhibits better performances [21], [22]. However, nanowire MOSFET geometries like triangular and hexagonal usually suffer from large gate leakage current (I G ) due to high gate electric field at the sharp corners [23]- [25].…”
Section: Introductionmentioning
confidence: 99%